Fatigue load testing of full-scale dynamic message signs. (1st January 2021) - Seo, Junwon; Amatya, Ibin
Highlights: Fatigue load testings of two full-scale dynamic message signs (DMSs) were tested. The tested DMSs include one DMS with adhesive joints and one DMS with welded joints. Strain, displacement, and load were recorded during each test to analyze the fatigue performance of tested DMSs. All the stress ranges were significantly below the thresholds of DMS panels from the S-N curves. Any damage was not observed in both the adhesive and welded DMSs due to the fatigue loadings. Abstract: This paper summarizes results acquired from the fatigue testings of two full-scale dynamic message signs (DMSs) fabricated by a local manufacturer in the United States. One DMS with adhesive joints and one DMS with welded joints were tested with fatigue loading. For the testing, each of the DMSs was loaded up to 500, 000 cycles with a force ranging between 0.249 kN and 0.818 kN equivalent to the design natural wind gust pressure based on a yearly mean speed of 18.02 km/h according to the AASHTO LRFD Specifications for Structural Supports for Highway Signs, Luminaires and Traffic Signals. Strain, displacement, and load were recorded during each test to analyze the structural adequacy of tested DMSs. During the testing, all the stress ranges observed in each of the tested DMSs were considerably below the threshold of the DMS panel, which was determined by generating its S-N curves. The maximum deflection range was found to be highest near the center for both adhesive and welded DMSs when encountered with the fatigue loads. It is recommended that additional stiffeners be installed to reduce the deflection range of the DMS at the center. It was also found that any damage was not observed in both the adhesive and welded DMSs due to the fatigue loading.